Comportamento de misturas compostas com fíleres carbonáticos frente à carbonatação - Fante, Munique (Universidade do Vale do Rio dos Sinos, 2020)
Limestone filler is used as a substitute for clinker in cement mixtures in order to reduce carbon dioxide emissions in the environment and fill the voids of cement paste. Permissible substitution levels are increasing in Brazil, the maximum cement substitution content increased from 10% in 1990 to 25% in 2018. Depending on the mixture used, the durability of the concrete is modified. When the subject carbonation is approached, there are divergences in the depth of carbonation when using limestone compared to cements without addition. This work aims the use of different limestone filler contents in Portland cement mortars and pastes, with variation of the water/cement (w/c) ratio, aiming to evaluate the carbonation performance, relating to porosity and mechanical resistance. The chemical, mineralogical and physical characterizations of the materials used, Portland CP V cement and limestone were performed. Mechanical resistance and water absorption tests were carried out on non-carbonated samples and then the phenolphthalein, XRD, TG, petrographic analysis and reflectance spectroscopy tests on carbonated samples were performed. The limestone filler is suitable for use, presenting the minimum content of calcite present and particle size lower than cement. Resistance and absorption tests pointed out 25% limestone as ideal for better performance. Phenolphthalein spray test showed a higher carbonation ratio linked to w/c ratio than to the amount of filler presence. XRD and TG tests showed the consumption of portlandite and calcite formation, as well as the appearance of other calcium carbonate polymorphs in accelerated carbonation after 28 days. Petrographic analysis test did not allow the sharp carbonation front to be distinguished and the reflectance spectroscopy test points to the carbonate presence.
Keywords: Fíler calcário calcítico; Carbonatação; Carbonato de cálcio; Polimorfos do carbonato de cálcio; Limestone filler; Carbonation; Calcium carbonate; Calcium carbonate polymorphs; ACCNPQ::Engenharias::Engenharia Civil